Penyebab Implikatur Percakapan Wacana Humor Berbahasa Jawa pada Rubrik Thengil di Majalah Ancas - Imaniah Kusuma Rahayu (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of the research is to explain the causes of implication in the rubric Thengil in the Ancas magazine. The collection data use refer method n written method. The analyze data use heuristic method n pragmatic method. The research approach is using methodologic theory. The data has been analyzed then presented informally. Informal presentation data can be done by using words. The cause implication found in this study are violations of the principle of cooperation and the principle of harmony. Violation of the principle of cooperation includes violation of quantity thimble, violation of quality thimble, violation of thimble relevance, and violation of the way thimble. The violation principle of harmony includes violation of respectful thimbles, violation of humble thimbles, violation of place aware of thimbles, and violation of tolerant thimbles. The cause implication found can serve as support for funny humor.